2002
DOI: 10.1103/physrevlett.89.156103
|View full text |Cite
|
Sign up to set email alerts
|

Polymers near Metal Surfaces: Selective Adsorption and Global Conformations

Abstract: We study the properties of a polycarbonate melt near a nickel surface as a model system for the interaction of polymers with metal surfaces by employing a multiscale modeling approach. For bulk properties, a suitably coarse-grained bead-spring model is simulated by molecular dynamics methods with model parameters directly derived from quantum chemical calculations. The surface interactions are parametrized and incorporated by extensive quantum mechanical density functional calculations using the Car-Parrinello… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
154
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 16 publications
0
154
1
2
Order By: Relevance
“…The behavior of these molecules on Si is very different to their behavior on Ni͑111͒. The adsorption energy of benzene on Ni is 1.05 eV, 34 which is comparable to the adsorption energy of benzene on Si. The geometries, however, are very different, and on the Ni surface the benzene remains relatively undistorted at a center-of-mass distance of 2 Å.…”
Section: Summary and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The behavior of these molecules on Si is very different to their behavior on Ni͑111͒. The adsorption energy of benzene on Ni is 1.05 eV, 34 which is comparable to the adsorption energy of benzene on Si. The geometries, however, are very different, and on the Ni surface the benzene remains relatively undistorted at a center-of-mass distance of 2 Å.…”
Section: Summary and Discussionmentioning
confidence: 90%
“…34,35 The first-principles calculations showed that benzene binds strongly to the Ni surface but that carbonic acid and propane experience significant repulsion. The behavior of these molecules on Si is very different to their behavior on Ni͑111͒.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the dualresolution modeling approach for studying the behavior of polymers near metal surfaces [22,23,24], for example, polymer chain ends that interact with the metal surface are represented partially atomistically while the remaining parts of the polymers, where lower resolution is adequate, are represented as bead-spring chains. However, the switching between different levels of resolution, i.e, the atomic and mesoscopic, is not allowed during the course of that MD simulation, and therefore the initial level of detail and thereby the number of degrees of freedom in the system remain unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Most simulations of the organic molecules-metal surfaces interactions are from the ab initio calculation and density functional theory (DFT) [11][12][13][14], which developed the potentials for the molecules between metals, but they are limited in a rather small scale. By MD methods, Braun et al [15] simulated multi-peptides interacting with gold of 5 ns.…”
Section: Introductionmentioning
confidence: 99%